Pd@TiO2/carbon nanohorn electrocatalysts: reversible CO2 hydrogenation to formic acid. Issue 6 (17th April 2018) - Melchionna, M.; Bracamonte, M. V.; Giuliani, A.; Nasi, L.; Montini, T.; Tavagnacco, C.; Bonchio, M.; Fornasiero, P.; Prato, M.
Abstract : Direct conversion of carbon dioxide to formic acid at thermodynamic equilibrium is an advantage of enzymatic catalysis, hardly replicated by synthetic analogs, but of high priority for carbon-neutral energy schemes. Abstract : Direct conversion of carbon dioxide to formic acid at thermodynamic equilibrium is an advantage of enzymatic catalysis, hardly replicated by synthetic analogs, but of high priority for carbon-neutral energy schemes. The bio-mimetic potential of totally inorganic Pd@TiO2 nanoparticles is envisioned herein in combination with Single Walled Carbon NanoHorns (SWCNHs). The high surface nano-carbon entanglement templates a wide distribution of "hard-soft" bimetallic sites where the small Pd nanoparticles (1.5 nm) are shielded within the TiO2 phase (Pd@TiO2 ), while being electrically wired to the electrode by the nanocarbon support. This hybrid electrocatalyst activates CO2 reduction to formic acid at near zero overpotential in the aqueous phase (onset potential at E < −0.05 V vs. RHE, pH = 7.4), while being able to evolve hydrogen via sequential formic acid dehydrogenation. The net result hints at a unique CO2 "circular catalysis" where formic acid versus H2 selectivity is addressable by flow-reactor technology.